Sustainable development of rural settlements. Role of EU funds in managing territorial disparities - Gaman, Florian; Emanuel Răuță; Oana Luca; Carmen-Mihaela Boteanu (Technium Social Sciences Journal, 2020)
The paper aims to perform an up-to-date radiography of the rural settlements in Romania, focusing on the main dysfunctions related to: employment, social exclusion and risk of poverty, education, health and infrastructure. Based on the overview, the article is developing scenarios for reducing the above dysfunctions, setting the scene and involving the proper actors for improving the quality of life in rural settlements, together with the potential funds dedicated for the present and future programming period.